On How to Frame The Object of Controversy in The Audience prior to The Ordinary Trial - de Miranda Vázquez, Carlos (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2018)
Among other factors the specific, accurate and efficient framing of the object of controversy clearly leads to the good quality of the initial sentence. Therefore, this procedural activity, as part of the requirements of the audience prior to it proves to be fairly important. Also, the latter is ruled by a precept, art. 428 of Civil Prosecution Law, which has a number of problems in its wording as when to be implemented in forensic law. So, the reason for this study is to take inventory of such inconvenience and to suggest likely solutions to them. All in all we aim at contributing toward an improvement of the ruling of the activity which frames the object of controversy and eventually to the improvement of such useful tool toward the good quality of civil law practice.